The use of international studies within the framework of the updated content of secondary education of the Republic of Kazakhstan - Akbayeva, G.N.; Sadykova, A.Ye.; Akkerman, E.O. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The article is about the use of international research in the context of the updated content of secondary education in the Republic of Kazakhstan, as an effective form of assessing the students' knowledge. The authors analyzed the features, key aspects of the standard on the renewed content of education, the main point of which is the system of criterial evaluation. Considered such concepts as TIMSS, PISA, CLIL technology. Analysis of conducted research in 2015 in Kazakhstan was also presented, on the subject of the similarities and differences of secondary education systems of various countries on the issue of the number of hours devoted to the study of the disciplines of science and humanitarian cycles; current state and level of functional, reading, natural science, mathematical literacy of schoolchildren. The authors attempted to substantiate the effectiveness of using CLIL technology in teaching subjects of the natural-science cycle. This led to the conclusion that to bring the structure and content of the Kazakhstan education in line with international standards and in the context of integration into the international educational space, taking into account the European Qualifications Framework, on the improvement of secondary education, the International Standard Classification of Education, the results of international comparative study TIMSS, PISA, CLIL and others, which allow to achieve positive results in training the younger generation.
Қазақстан Республикасының жаңартылған орта білім мазмұны шеңберінде халықаралық зерттеулерді пайдалану
Использование международных исследований в рамках обновленного содержания среднего образования Республики Казахстан
Keywords: integration; international research; concept; TIMSS; PISA; CLIL; competence approach; criterial evaluation; content; communication; cognition; culture